Building Real-Time Fraud Detection Systems with Azure AI for Financial Services - Sudeep Annappa Shanubhog, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive framework for implementing real-time fraud detection systems in financial services using Azure AI technologies. The article explores the integration of advanced machine learning algorithms, stream processing architectures, and security frameworks to combat increasingly sophisticated financial fraud schemes. The article details the core components of AI-powered detection architecture, including transaction pattern analysis, behavioral anomaly detection, and adaptive risk scoring methodologies. The article incorporates MLOps practices for model deployment, lambda architecture for stream processing, and zero-trust security principles for comprehensive system protection. Through extensive case studies and performance analysis, the article demonstrates how AI-enhanced fraud detection systems significantly improve detection accuracy while reducing false positives and operational overhead. The article also addresses critical challenges in regulatory compliance, data protection, and system scalability, providing practical solutions for financial institutions implementing such systems. This article contributes to the evolving field of financial security by presenting a scalable, efficient, and secure approach to real-time fraud detection. Introduction
Keywords: Fraud Detection Systems; Azure AI; Machine Learning; Real-time Processing; Financial Security